Alpine subduction zone metamorphism in the Palaeozoic successions of the Monti Romani (Northern Apennines, Italy). (25th January 2022) - Papeschi, Samuele; Pontesilli, Alessio; Romano, Claudia; Rossetti, Federico; Theye, Thomas
Abstract: The hinterland of the Cenozoic Northern Apennines fold‐and‐thrust belt exposes the metamorphic roots of the chain, vestiges of the subduction‐related tectono‐metamorphic evolution that led to the buildup of the Alpine orogeny in the Mediterranean region. Like in other peri‐Mediterranean belts, the tectono‐metamorphic evolution of the Palaeozoic continental basement in the Apennines is still poorly constrained, hampering the full understanding of their Alpine orogenic evolution. We report the first comprehensive tectono‐metamorphic study of the low‐grade metasedimentary (metapsammite/metapelite) succession of the Monti Romani Complex (MRC) that formed after Palaeozoic protoliths and constitutes the southernmost exposure of the metamorphic domain of the Northern Apennines. By integrating fieldwork with microstructural studies, Raman spectroscopy on carbonaceous material and thermodynamic modelling, we show that the MRC preserves a D1 /M1 Alpine tectono‐metamorphic evolution developed under HP–LT conditions ( 1.0–1.1 GPa at T 400°C) during a non‐coaxial, top‐to‐the‐NE, crustal shortening regime. Evidence for HP–LT metamorphism is generally cryptic within the MRC, dominated by graphite‐bearing assemblages with the infrequent blastesis of muscovite ± chlorite ± chloritoid ± paragonite parageneses, equilibrated under cold palaeo‐geothermal conditions ( 10°C/km). Results of this study allow extending to the MRC the signature of subduction zone metamorphism already documented in the hinterland of the Apennine orogen, providing further evidence of the syn‐orogenic ductile exhumation of the HP units in the Apennine belt. Finally, we discuss the possible role of fluid‐mediated changes in the reactive bulk rock composition on mineral blastesis during progress of regional deformation and metamorphism at low‐grade conditions.